Exploring demographic, lifestyle, and learning motivation factors in predicting high school students’ tax awareness - Ismail Khozen; Prianto Budi Saptono; Arfah Habib Saragih; Wulandari Kartika Sari; Adang Hendrawan; Milla Sepliana Setyowati (Universitas Negeri Surabaya, 2026)
While many studies have examined tax education and compliance, few have investigated how psychological and lifestyle factors during adolescence shape tax awareness. This study argues that tax understanding is influenced not only by formal economic literacy but also by learning motivation, self-discipline, and social context. Using Purwokerto as a case study, this research analyzes the effects of demographic, lifestyle, and learning motivation factors on high school students’ tax awareness. Data were collected from 285 students through an online survey and analyzed using multiple linear regression. The results indicate that gender, grade level, healthy food consumption, and learning motivation significantly affect tax awareness, whereas family socioeconomic factors do not. These findings suggest that personal behavior and motivation play a more critical role in shaping adolescents’ tax awareness and provide a foundation for developing contextual and character-based tax education in secondary schools.